The abundance and types of plankton in milkfish ponds at Banyuasin South Sumatera - Mirna Fitrani; Reni Septiyani; Dade Jubaedah; Marini Wijayanti; Annisa Septimesy; Yenni Sri Mulyani (Depik, 2023)
Tidal lowland is an area with significant potential for fisheries development, especially in aquaculture. Abundant water supply and land availability provide great opportunities for cultivating aquaculture commodities such as fish, shrimp, and crab. However, effective water quality management poses a significant challenge, necessitating a comprehensive evaluation based on biological, physical, and chemical assessment. Among the crucial parameters influencing water fertility, the presence of plankton stands out. Therefore, this study aimed to investigate water fertility by identifying plankton species, abundance, diversity, dominancy, and water quality in milkfish ponds at Banyuasin, South Sumatra. The results showed that the abundance of phytoplankton and zooplankton ranged from 1030-1791 individual L-1 and 103-461 individual L-1, respectively. Furthermore, Bacillariaceae was recorded to be the highest specie, followed by Cyanophyta, Chlorophyta, Protozoa, Rotifer, and Arthropoda. The range diversity index varied between 1 to 2.6, while the density and dominance indices ranged from 0.9 and 1, as well as 0.1 and 0.8, respectively. The classification of the pond's fertility fell within the mesotrophic category, signifying a moderate level. In conclusion, the water quality maintained an optimum range, thereby supporting the growth of plankton and milkfish. Meanwhile, only ammonia was below the optimum range stipulated by PP No. 22 of 2021 suggested.Keywords:bioindicatormilkfishplanktontidal lowlandwater quality